1991
DOI: 10.3382/ps.0701281
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Endogenous Viral Gene Patterns in White Leghorn, Medium Heavy, White Plymouth Rock, and Cornish Chickens

Abstract: The endogenous viral (ev) gene patterns of White Leghorn (WL; 6 lines), medium heavy (MH; 4 lines), White Plymouth Rock (WPR; 8 lines), and Cornish types (2 lines) of commercial chickens were compared. Southern blot analysis of SstI-digested genomic DNA of 151 chickens revealed that the number of ev gene-containing fragments in a chicken from the MH, WPR, or Cornish type is about twice twice the number of that in WL chickens. Also, the number of hybridizing fragments of different size found within one line was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…We cannot explain the difference in frequency in TVB alleles in broilers versus egg-laying strains, but it is of interest that numerous studies have shown that the number and frequency of ALV-E genes is generally higher in broilers than in egg-laying strains (Ignjatovic, 1986; Kuhnlein et al, 1989;Aarts et al, 1991;Gavora, et al, 1991;Sabour et al, 1992). Indeed, Benkel (1998) has stated that the average modern egg chicken has only one to three ALV-E elements, whereas meat birds typically carry six to 10.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot explain the difference in frequency in TVB alleles in broilers versus egg-laying strains, but it is of interest that numerous studies have shown that the number and frequency of ALV-E genes is generally higher in broilers than in egg-laying strains (Ignjatovic, 1986; Kuhnlein et al, 1989;Aarts et al, 1991;Gavora, et al, 1991;Sabour et al, 1992). Indeed, Benkel (1998) has stated that the average modern egg chicken has only one to three ALV-E elements, whereas meat birds typically carry six to 10.…”
Section: Discussionmentioning
confidence: 99%
“…Noninbred Leghorns usually have one to five ev loci (Rovigatti and Astrin, 1983;Aarts et al, 1991), but some have none (Astrin et al, 1979;Gavora et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…An eul-specific probe showed that the genomic insertion site for eul was not occupied by a viral insert in Fayoumi chickens although they carried the restriction fragments usually associated with an eul occupied site in White Leghorns, ie 9.5 kb with SacI and 5.2 kb with BamHI (Lamont et al, 1992). A similar approach revealed a much lower frequency of occupation of the eul site in White Plymouth Rock chickens than in White Leghorns (Aarts et al, 1991). The polymerase chain reaction has recently been proposed as a method to identify ALV-related ev genes in a locus-specific way (Benkel et al, 1992 Leghorn (Hughes et al, 1981).…”
mentioning
confidence: 99%
“…Furthermore, the finding of a deletion in the gag region was useful to confirm the identification of ev6 in all the strains. Deletions within the gag region were found to be rare in a survey of several strains (Aarts et al, 1991) but more frequent in White or Brown Leghorns (Hughes et al, 1981;Gudkov et al, 1986;Ronfort et al, 1991 (Iraqi et al, 1991) and commercial broilers (Boulliou et al, 1991). This could suggest that ev6 is a very old retroviral insertion.…”
mentioning
confidence: 99%
See 1 more Smart Citation